DESIGN OF MECHANISM AND MOTION SYSTEM ON TANK PROTOTYPE USING ODOMETRY - Abdul Rahman; Mohammad Zaenal Arifin; Gesit Pratiknyo; Bagus Irawan (JOURNAL ASRO, 2020)
At present, Indonesia's defense forces are not yet on par with European countries. The size is the variation of Indonesia's defense equipment technology that has not been able to keep up with the defense equipment of European countries . Utilization of unmanned tank rides is a solution in empowering mobile combat equipment as a means of national defense and defense . Unarmed armored tank defense equipment as a means of national defense and defense . The Odometry technique applied in this study uses an encoder sensor device mounted on the two right and left wheels of the prototype tank. Wheel movement will produce the number of turns that can be calculated using an encoder sensor . the authors use odometry techniques aimed at estimating distances to destinations within a relatively small measurement area, in the wider measuring area this study uses GPS. Another goal is to get the accuracy and accuracy of distance measurements against the destination location . The results obtained in this study are the level of accuracy of the measurement of distance traveled in units of cm from the results of testing and implementation of the odometry system . The application of odometry is used to get the calculation of the change in distance due to the displacement of the prototype location during the autopilot motion process in relation to getting the accuracy of moving the position towards the waypoint . The measurement error rate obtained is less than 1%. It is expected that this system can be used as a motion mechanism system on alutsi s ta tank. Keywords : Odometri, Encoder , Waypoint, Autopilot